Heat treatments for complex bronze aluminum, martensitic transformation and kappa phase – hardenability - Rosario Francia, Samuel (2011)
The aluminum bronzes are cooper based alloys which contains generally from 8.0% to 12.0% of aluminum. When you add elements such as iron, nickel and manganese along with the phase alpha (α) which is rich in copper and the eutectoid alpha/ gamma2 (α/γ2), it appears precipitations whose nature depends on the elements added quantity, with slow cooling in the sand’s molds (50 ºC/min), are presented alpha.beta´ (α.β´) or alpha, beta´. gamma2 (α, β´.γ2) which because of the different shapes that the precipitations have, they are simplified in k1, k2, k3, k4. For the fusion, it is required a greater care because of its tendency to absorb hydrogen, they respond to heat treatments of quenching and tempering reaching a hardness between 90 Brinell (56 RcB) and 390 Brinell (42 Rc C) always that the k phases are dissolved or uniformly distributed in the main phase.